Active recovery during gymnastics session - Jemni, M.; Sands, W. A.; Friemel, F. (2003)
During intense gymnastic sessions, gymnasts produce moderately high lactate values. This study shows that a combined recovery inserted between repetitions may be of great importance to the gymnast. Lactate clearance is higher when gymnasts used 5 min rest and 5 min self-selected active recovery with intensity below the lactate threshold. Gymnasts improved their performance when using this kind of recovery. This recovery may be used during the competitive period in which gymnasts usually have to repeat their six events more than twice in one session which is common during training and simulated competitions during training. Because gymnastics shows a relatively high injury rate, and fatigue is often related to injury, this may assist gymnasts in reducing the likelihood of injury.